STRATEGI ADAPTASI MENJADI SINGLE MOTHER (STUDI DESKRIPTIF KUALITATIF PEREMPUAN SINGLE MOTHER DI DESA CEPOKOSAWIT KECAMATAN SAWIT KABUPATEN BOYOLALI - Rahayu, Alfina (ISSN.2252-8407)
ABSTRACTThis research aims to determine (1) the meaning of women in the life of being a single mother in the village community Cepokosawit; (2) the implementation of economic strategies doing single mother as a single parent in maintaining the survival of his family in Cepokosawit village. This research used descriptive qualitative method to produce and process the research data descriptive nature, such as transcripts of interviews and observations. The population in this study are all citizens of the women in Cepokosawit village, Sawit district, Boyolali regency. The selected Informants were several single mothers in Cepokosawit village. The technique of taking informants using purposive sampling based on certain criteria, (1) the informant is a single mother who has been separated from her husband for at least four years; (2) has a dependent school child and unmarried; (3) comes from a medium family . The collection of data carried out by interview and observation of the life of a single mother in their role as the main breadwinner of the family. Data analysis technique is done by means of data collection, data reduction, data display and drawing conclusions or data verification . The results of this research are, First, the meaning of a single mother in Cepokosawit village is a tough woman who has a high fighting spirit alive. Forms of toughness and high living struggle can be seen from how a single mother in handling the domestic realm that is taking care of the house and educate children alone as well as in the public domain serves as a hard fighter backbone of the family. Second, the economic adaptation strategies in a single mother family visible in how they align with the amount of income a family needs every day of his life. Forms of economic planning is also evident from the way a single mother to save, set aside in part piecemeal revenue that could be used to meet the needs of their child's education and are used for urgent needs. Most single mother who can not save their children's education costs and the shortage will ask for help to relatives who are more capable.  Keywords: family, strategy, single mother